Hemodynamic changes in a middle cerebral artery aneurysm at follow-up times before and after its rupture: a case report and a review of the literature - Sejkorová, Alena; Dennis, K D; Švihlová, Helena; Petr, O; Lanzino, G; Hejčl, A; Dragomir-Daescu, D (Neurosurgical review, 2017)
Hemodynamic parameters play a significant role in the development of cerebral aneurysms. Parameters such as wall shear stress (WSS) or velocity could change in time and may contribute to aneurysm growth and rupture. However, the hemodynamic changes at the rupture location remain unclear because it is difficult to obtain data prior to rupture. We analyzed a case of a ruptured middle cerebral artery (MCA) aneurysm for which we acquired imaging data at three time points, including at rupture. A patient with an observed MCA aneurysm was admitted to the emergency department with clinical symptoms of a subarachnoid hemorrhage. During three-dimensional (3D) digital subtraction angiography (DSA), the aneurysm ruptured again. Imaging data from two visits before rupture and this 3D DSA images at the moment of rupture were acquired, and computational fluid dynamic (CFD) simulations were performed. Results were used to describe the time-dependent changes of the hemodynamic variables associated with rupture. Time-dependent hemodynamic changes at the rupture location were characterized by decreased WSS and flow velocity magnitude. The impingement jet in the dome changed its position in time and the impingement area at follow-up moved near the rupture location. The results suggest that the increased WSS on the dome and increased low wall shear stress area (LSA) and decreased WSS on the daughter bleb with slower flow and slow vortex may be associated with rupture. CFD performed during the follow-up period may be part of diagnostic tools used to determine the risk of aneurysm rupture.
Keywords: Models, Cardiovascular; Subarachnoid Hemorrhage; subarachnoidální krvácení; Hemodynamics; modely kardiovaskulární; Humans; Female; Imaging, Three-Dimensional; lidé; Aneurysm, Ruptured; Middle Aged; ženské pohlaví; lidé středního věku; hemodynamika; Angiography, Digital Subtraction; Intracranial Aneurysm; intrakraniální aneurysma; zobrazování trojrozměrné; prasklé aneurysma; digitální subtrakční angiografie